2004
DOI: 10.1002/qua.20143
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Gaussian basis sets: Variationally optimized s‐type sets for the open‐shell systems HeH and BeH

Abstract: Distributed basis sets of s-type

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…This makes it possible to minimize the error associated with truncation of one-particle basis sets and, thus, to observe more clearly the errors of the method itself. More information about of such basis sets can be found in [14,15]. We compare our results with those of the precisional ab initio calculations obtained with extended basis sets and experimental data [16,17].…”
Section: Applications To Electronic Excitation Energiesmentioning
confidence: 50%
“…This makes it possible to minimize the error associated with truncation of one-particle basis sets and, thus, to observe more clearly the errors of the method itself. More information about of such basis sets can be found in [14,15]. We compare our results with those of the precisional ab initio calculations obtained with extended basis sets and experimental data [16,17].…”
Section: Applications To Electronic Excitation Energiesmentioning
confidence: 50%
“…Although the parameters defining the basis sets, ζ k p and R k p , can be determined by invoking the variation principle [92][93][94][95], it has been established that the even-tempered prescription in which the exponents are taken to form a geometric sequence:…”
Section: Distributed Gaussian Basis Sets For Ground and Excited Statesmentioning
confidence: 99%
“…In our previous papers [44][45][46], we have presented variationally optimized distributed Gaussian basis sets containing only functions s-type for some simple molecules. We demonstrated that a sub-µ Hartree level of accuracy can be supported by basis sets of modest size.…”
Section: Comparison Of the Anharmonic Distribution With Variationallymentioning
confidence: 99%
“…The emphasis of our recent investigations for small diatomic molecules [44][45][46] was to design fully optimized s-type distributed basis sets capable of supporting energies of sub-µHartree accuracy at the Hartree-Fock level. Certainly, such variational calculations involve a time-consuming nonlinear optimization process for both exponents and positions and cannot be used for routine calculations on arbitrary systems.…”
Section: Introductionmentioning
confidence: 99%